2012
DOI: 10.1080/21513732.2012.671191
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of provisioning services of the Ga-Mampa wetland, South Africa, to local livelihoods

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…Our study underscores the importance of estimating the monetary value of wetland ecosystems and can be compared to values from similar studies of African wetlands (see Emerton et al (1999);Seyam et al (2001); Lannas and Turpie (2009);Turpie et al (1999); Rebelo et al (2010); Adekola et al (2012)). Monetary values per unit area ($/ha/year) and per household ($/hh) in our study are generally higher than those reported in these studies (Table 2), which is likely due to the extent of the Niger Delta wetlands, and the level of dependence of the local community upon them compared to the other smaller wetlands.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Our study underscores the importance of estimating the monetary value of wetland ecosystems and can be compared to values from similar studies of African wetlands (see Emerton et al (1999);Seyam et al (2001); Lannas and Turpie (2009);Turpie et al (1999); Rebelo et al (2010); Adekola et al (2012)). Monetary values per unit area ($/ha/year) and per household ($/hh) in our study are generally higher than those reported in these studies (Table 2), which is likely due to the extent of the Niger Delta wetlands, and the level of dependence of the local community upon them compared to the other smaller wetlands.…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with other studies (Lannas and Turpie 2009;Rebelo et al 2010), but are considerably higher than that of some other African studies. For the Ga-Mampa wetland in South Africa 16% of the total value of the wetland was generated as cash income (Adekola et al 2012); 17% in the Barotse wetland, Zambia, 13% in the Chobe-Caprivi wetlands, and 15% in Malawi's Lower Shire wetlands (Turpie et al 1999). Our study shows that the cash generating potential of wetland ecosystem services could be much higher than previously thought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that wetlands are vital for local households has been supported by many other studies, but it is important to realise that the contribution of services varies strongly per country and region, depending on the local socio-economic and environmental context. This is underlined by a new study by Adekola et al (2012), who quantified the contribution 188 Editorial of provisioning services to local livelihoods by a relatively small (1 km 2 ) wetland in South Africa. Through a number of interesting data collection approaches, the authors were able to estimate that the wetland's contribution to local people's income represented about 15% of the average 2006 household income.…”
mentioning
confidence: 99%